Performance Analysis of GPON ONT-OLT Interoperability in Multi-Vendor FTTH Environment - GUNADI DWI HANTORO; ANDI WAHYUDI; WIDYA KAMALA; FEBRIZAL UJANG (ELKOMIKA: Jurnal Teknik Energi Elektrik, Teknik Telekomunikasi, & Teknik Elektronika, 2026)
Interoperability between Optical Line Terminals (OLTs) and Optical Network Terminals (ONTs) is an important aspect of GPON-based Fiber to the Home (FTTH) deployments in multi-vendor environments. Although the ITU-T G.984 standard defines an interoperability framework, variations in OMCI implementation and device management mechanisms across vendors may still affect service performance. This study aims to evaluate the interoperability of a Vendor A ONT with four OLT platforms through OMCI registration testing, Layer-2 configuration, ACS activation, and verification of data, voice, and video services. The test results show that all evaluation stages were successfully completed with a 100% success rate across all OLT platforms, and that service performance remained stable without significant degradation. These findings confirm that the Vendor A ONT complies with the ITU-T G.984 standard and can be reliably deployed in multi-vendor GPON networks.